Substrate analogues and inhibition of ACC oxidase: Conversion of D-valine to iso-butanal - Gibson, E; Zhang, Z; Baldwin, J; Schofield, C (1998)
Amino acids and their hydroxamates were studied as inhibitors of purified recombinant 1-aminocyclopropane-1-carboxylic acid (ACC) oxidase (tomato). Neither L-valine, L-alanine, L- nor D-isoleucine displayed inhibition, but D-valine and D- alanine were weak inhibitors of ACC oxidase catalysed conversion of ACC to ethylene. GC-MS analysis showed that D-valine was converted to iso-butanal. In contrast to studies using native ACC oxidase (apple), inhibition of recombinant ACC oxidase (tomato) by amino acid hydroxamates appears to result (at least predominantly) from chelation of free iron in solution.